2019
DOI: 10.1021/jacs.8b13023
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Active Site Architecture for O2 Activation in the Ergothioneine Biosynthetic EgtB from Chloracidobacterium thermophilum

Abstract: Sulfoxide synthases are non-heme iron enzymes that catalyze oxidative carbon-sulfur bond formation between cysteine derivatives and N-a-trimethylhistidine as a key step in the biosynthesis of thiohistidines. The complex catalytic mechanism of this enzyme reaction has emerged as the controversial subject of several biochemical and computational studies. These studies all used the structure of the g-glutamyl cysteine utilizing sulfoxide synthase, MthEgtB from Mycobacterium thermophilum (EC 1.14.99.50), as a stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 51 publications
1
59
0
Order By: Relevance
“…The same compound has been implicated as an intermediate in the biosynthesis of 2 by S. pombe . In the presence of 0.5 m m SeCys and 0.5 m m TMH, Cth EgtB produces 4 at a rate of (1.2±0.2)×10 −3 s −1 (Figure S3, Supporting Information) which is roughly 200‐fold slower than formation of sulfoxide 3 under the same conditions . We did not observe selenoxide 5 , which is not surprising because selenoxides are rapidly reduced in the presence of selenols, ascorbate or TCEP…”
Section: Resultsmentioning
confidence: 50%
See 3 more Smart Citations
“…The same compound has been implicated as an intermediate in the biosynthesis of 2 by S. pombe . In the presence of 0.5 m m SeCys and 0.5 m m TMH, Cth EgtB produces 4 at a rate of (1.2±0.2)×10 −3 s −1 (Figure S3, Supporting Information) which is roughly 200‐fold slower than formation of sulfoxide 3 under the same conditions . We did not observe selenoxide 5 , which is not surprising because selenoxides are rapidly reduced in the presence of selenols, ascorbate or TCEP…”
Section: Resultsmentioning
confidence: 50%
“…We have previously described the crystal structure of Cth EgtB and shown that this type of bacterial sulfoxide synthase accepts TMH and Cys as substrates . At neutral pH and at room temperature, Cth EgtB produces sulfoxide 3 as the main product (80 %) and cysteine dioxide as a minor product ( 6 , 20 %, Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The evolutionary emergence of type II CDOs was probably facilitated by the fact that a single point mutation in sulfoxide synthases suffice to elicit efficient thiol dioxygenase activity. [21,22] As DsqCDO retained the ability to bind TMH, we wondered as to whether mutating Phe442 to Tyr would restore sulfoxide synthase activity. To address this question, we examined the corresponding variant (DsqCDO F442Y ) by the same methodology as described above.…”
Section: The F442y Mutantmentioning
confidence: 99%